Estudo experimental do processo de rotomoldagem: efeitos sobre a morfologia e estabilidade dimensional - Comisso, Tiago Boni (2011)
In the present study the warpage of rotationally molded parts of a linear low density polyethylene (LLDPE) was investigated. The effect of different processing factors as part thickness, cooling condition and diameter of the venting tube was evaluated. In addition to the rotational molding experiments, an alternative experimental technique, denominated “Hot Press”, was also applied to investigate the warpage of two different grades of LLDPE under typical rotational molding conditions, which means slow cooling from only one side. Crystallinity and spherulitic morphology along the thickness of the rotationally molded parts were studied by Differential Scanning Calorimetry and Polarized Light Optical Microscopy. It is shown that the warpage increases with the increase of the cooling rate. Increase of diameter of the venting tube is more effective in reducing the warpage of rotationally molded parts mainly for lower cooling rates. In hot press experiments the grade of LLDPE with lower melt flow index and higher flexural strength presented lower warpage. Part thickness affects the warpage in hot press experiments only for faster cooling rates. In general, crystallinity and spherulitic diameter are lower in positions along the rotationally molded part thickness where the cooling rate is faster.